E-region ionospheric storm on May 1–3, 2010: GSM TIP model representation and suggestions for IRI improvement. Issue 8 (15th April 2015) - Bessarab, F.S.; Korenkov, Yu.N.; Klimenko, V.V.; Klimenko, M.V.; Zhang, Y.
Abstract This paper presents the model simulation results of ionospheric E-region parameters during geomagnetic storm on May 2–3, 2010. For this investigation we used the Global Self-consistent Model of the Thermosphere, Ionosphere and Protonosphere (GSM TIP) developed in West Department of IZMIRAN. GSM TIP model simulations were performed using empirical model of high-energy electron precipitation. The temporal and spatial distributions of the lower ionosphere parameters and minor neutral species are presented. GSM TIP model results of E-region parameters are compared with IRI-2012 model. The differences between model results are discussed.